Vectors of the dynamics of agribusiness according to land use in the municipality of Pergamino in the Pampean Region of Argentina - Leavy, Sebastian (Universidad Nacional del Litoral, 2022)
This research analyses the dynamics of the local system, aiming the anticipation of future scenarios of agribusiness of Argentina Pampas. Prospective analysis of the SAG aims to train the main stakeholders linked to land use in the county of Pergamino to the possible changes that may occur in the future. The characterization of the vectors of the agribusiness dynamics of Pergamino County was carried out by identifying the main stakeholders, the key variables that underline the evolution of agribusiness systems and their interrelationships, correlating them with the trends of each one of the link-sectors of this agribusiness system. The identification and analyses of these elements are the preliminary steps in the construction of the future scenarios of the agribusiness in the county. The methodology is based on the use of 49 semi-structured interviews with the main stakeholders. The conclusion of this research is that the structural changes in the county of Pergamino agribusiness system are generated mainly by international stakeholders. A total of 24 key variables were identified as relevant to the county agribusiness future. It is concluded that the structural changes in the SAG of the Pergamino municipality are generated mainly by international actors. It is revealed that, for the local economy, the importance of variables related to the evolution of the market, business concentration and innovation are strong indicators of the insertion and international interdependence of Agribusiness in the Pampas region of Argentina.